Smart Monochromatic Composite: A Literature Review - Muhammad Adeel Ahmed; Rizwan Jouhar; Zohaib Khurshid (International Journal of Dentistry)
Over the previous years of the 20th and 21st centuries, there has been a progression in the field of bonded esthetic restorations. At the present time, the inclination of dentists toward the smart monochromatic shade of composite is flourishing owing to the fact that it decreases the requirement of a range of composite shades, curtails the waste of unconsumed composite shades, lessens chair side interval, abolishes the shade selection, and decreases dependency on shade-selecting methods. Smart monochromatic composite is known to obtain the color of the adjacent tooth structure in which it is placed. Therefore, the current literature elucidates the several features of innovative and revolutionary monochromatic composites including color stability, mechanical and optical properties, and shade-matching capability that could have a positive impact potentially over other resin composites.